Microwave assisted fluidized bed drying of bitter gourd: Modelling and optimization of process conditions based on bioactive components - Insha Zahoor; Aamir Hussain Dar; Kshirod Kumar Dash; R. Pandiselvam; Alexandru Vasile Rusu; Monica Trif; Punit Singh; G. Jeevarathinam (Food Chemistry: X, 2023)
Bitter gourds were dried under varied drying conditions in a microwave assisted fluidized bed dryer, and the process was optimized using response surface methodology. Microwave power, temperature and air velocity were used as process variables for drying and the process parameters were varied between 360 and 720 W, 40–60 °C and 10–14 m/s, respectively. The responses determined for deciding the optimal criteria were vitamin C, total phenolics, IC50, total chlorophyll content, vitamin A content, rehydration ratio, hardness and total color change of the dried bitter gourd. Statistical analyses were done by using response surface methodology, which showed that independent variables affected the responses to a varied extent. The optimum drying conditions of 550.89 W microwave power, 55.87 °C temperature, and 13.52 m/s air velocity were established for microwave assisted fluidized bed drying to obtain highest desirability for the dried bitter gourd. At optimum conditions, validation experiment was done to ensure the suitability of models. Temperature and drying time plays an important role in the deterioration of bioactive components. Faster and shorter heating led to the greater retention of bioactive components. Taking the aforesaid results into consideration, our study recommended MAFBD as a promising technique with minimum changes in quality attributes of bitter gourd.